(untitled) (Chittagong University Journal of Biological Sciences, 2024)
An extensive investigation on the diversity of wild edible vascular plants of Sandwip Island in Chittagong district, Bangladesh has been conducted during August 2008 to September 2011. The present study has revealed a total of 39 species of wild edible vascular plants under 27 genera in 19 families. The people used various wild vascular plant parts like leaves, stem, fruit etc. as a source of food in the studied area. Many rural people of the area are mostly dependent on wild vascular plants as their source of vegetables in their daily life. But, the wild vegetable resources of the area are decreasing day by day due to excessive collection of plants and habitat destruction. So, a documentation of these plant resources is needed in order to domesticate them for sustainable use. The Chittagong Univ. J. B. Sci.,Vol. 7(1 &2):11-20, 2012